The Fulfillment of Moral Rights and Economic Rights in the Commercial Use of Personal Portraits on Instagram - Alessandra de Rionny; Rika Lestari; Setia Putra (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2026)
This article examines the fulfillment of moral and economic rights in the commercial use of personal portraits on Instagram, where the rapid growth of digital business has intensified the unauthorized exploitation of visual content. This study aims to analyze the extent to which these rights are fulfilled and to identify commonly used dispute resolution mechanisms. The research employs a sociological legal method with a case approach, utilizing primary data obtained from 50 portrait owners and 15 business actors, supported by relevant literature. The findings reveal that the fulfillment of these rights remains inadequate, as many individuals receive only attribution without economic compensation and demonstrate limited awareness of their legal rights. Dispute resolution is predominantly conducted through informal and non-litigation mechanisms, such as direct communication and platform-based reporting, rather than formal legal processes. The novelty of this study lies in its focus on non-commercial individuals within a single social media platform, integrating empirical analysis with reward theory and principled negotiation theory. These findings underscore the urgency of strengthening legal awareness, improving enforcement, and enhancing the effectiveness of dispute resolution mechanisms to ensure more comprehensive protection of creators in the digital environment.